An Update Algorithm for Restricted Random Walk Clusters - Franke, Markus (KIT Scientific Publishing, 2007)
This book presents the dynamic extension of the Restricted Random Walk Cluster Algorithm by Schöll and Schöll-Paschinger. The dynamic variant allows to quickly integrate changes in the underlying object set or the similarity matrix into the clusters; the results are indistinguishable from the renewed execution of the original algorithm on the updated data set.